2018
DOI: 10.1038/s41379-018-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Salvaging the supernatant: next generation cytopathology for solid tumor mutation profiling

Abstract: With the expanding role of targeted therapy in patients with solid tumors, pathologists face the daunting task of having to maximize limited volume tissue obtained by fine needle aspiration for a variety of molecular tests. While most molecular studies on fine needle aspiration samples have been reported using cellular material, recent studies have shown that a substantial amount of DNA can be retrieved from the supernatant fluid of aspirate needle rinses after cell pelleting for cytospin or cell block prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 41 publications
6
54
0
Order By: Relevance
“…One hypothesis that has been proposed is that, due to the high turnover of tumor cells, the supernatant fluid is enriched in tumor‐derived cell‐free DNA . However, a qualitative analysis of the DNA extracted from supernatant fluid samples in our previous study demonstrated that the majority of the DNA retrieved from these samples comprised high molecular weight DNA, suggestive of cellular DNA, with only a small component likely representing cell‐free DNA . Therefore, our hypothesis is that the supernatant fluid DNA is likely derived from tumor cells that are lysed during the FNA procedure or during processing of the needle rinse at the time of centrifugation.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…One hypothesis that has been proposed is that, due to the high turnover of tumor cells, the supernatant fluid is enriched in tumor‐derived cell‐free DNA . However, a qualitative analysis of the DNA extracted from supernatant fluid samples in our previous study demonstrated that the majority of the DNA retrieved from these samples comprised high molecular weight DNA, suggestive of cellular DNA, with only a small component likely representing cell‐free DNA . Therefore, our hypothesis is that the supernatant fluid DNA is likely derived from tumor cells that are lysed during the FNA procedure or during processing of the needle rinse at the time of centrifugation.…”
mentioning
confidence: 82%
“…15 However, a qualitative analysis of the DNA extracted from supernatant fluid samples in our previous study demonstrated that the majority of the DNA retrieved from these samples comprised high molecular weight DNA, suggestive of cellular DNA, with only a small component likely representing cell-free DNA. 18 Therefore, our hypothesis is that the supernatant fluid DNA is likely derived from tumor cells that are lysed during the FNA procedure or during processing of the needle rinse at the time of centrifugation. The DNA yield and variant allelic frequency observed on NGS in our study 18 correlated with the tumor percentage noted in the cellular component of the FNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one recent study rigorously analyzed NGS of cytologic direct smears or liquid‐based preparations and found them to be comparable to FFPE core biopsies or cell blocks . Another intriguing potential sample source for NGS is the supernatant from fine needle aspiration needle rinses …”
Section: Sample Procurement and Preparationmentioning
confidence: 99%
“…25 Another intriguing potential sample source for NGS is the supernatant from fine needle aspiration needle rinses. 26…”
Section: Sample Procurement and Preparationmentioning
confidence: 99%